Business Plan Implementasi Freshtige Salad Buah (Implementasi Usaha Salad Buah di Kota Palembang) - Stephany, Stephany; Fernandes, Charles; Fadly, Jeremia Shalom; Pramuditha, Charisma Ayu (MDP Student Conference, 2025)
This study examines the marketing strategy and customer satisfaction of Freshtige, a fruit salad business targeting young consumers in Palembang. Using a quantitative approach, data were collected through surveys involving 74 respondents and secondary data analysis of Freshtige’s operational and financial records. The findings reveal that digital marketing, particularly through social media and influencer collaborations, plays a crucial role in increasing brand awareness and customer engagement. The majority of respondents expressed high satisfaction with the product quality, service, and purchasing experience, contributing to strong customer loyalty and repeat purchases. The study also highlights the importance of product innovation, as consumer interest in new fruit salad variants remains high. This research provides valuable insights for small businesses in the healthy food sector, emphasizing the need for continuous innovation, effective digital marketing strategies, and service quality to maintain business sustainability and growth.